Brand Old Association dan Persepsi Konsumen Gen Z pada Merek Nespresso - Rian Hidayatulloh Devansyah; Iksan, Muhamad (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines how brand old association influences Gen Z’s perceived quality of the Nespresso brand. It aims to analyze the overall effect of brand old association, its six dimensions, and the moderating role of brand information presentation. Using a quantitative approach with a within-subject experimental design, data were collected from 111 Gen Z respondents under blind test and correct information conditions. The findings show that brand old association has a positive and significant effect on perceived quality. Reminiscence and timelessness are significant dimensions, and the interaction between the two conditions is also significant. These results suggest that old brand associations can be strategic assets when communicated meaningfully to Gen Z. Keywords: Brand old association, Gen Z, consumer perception, perceived quality, Nespresso, brand image, coffee branding, experimental study